Tren Baru Perilaku Supervisi Pendidikan: Fenomena Pengawasan di Sekolah - Singgih Aji Purnomo; Zakiyatul Badriyah; Suharwanto (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
This paper is about the New Trend of Educational Supervision Behavior: The Phenomenon of Supervision in Schools. This paper focuses on the phenomenon of supervision in schools during the covid-19 pandemic. This research is qualitative research with a phenomenological approach. Data collection is done by observation and interview. From the data and information obtained analyzed by means of data reduction, display data, and inference. The data of this study is presented in the form of descriptive narratives equipped with argumentation. From the data of the results of the study, managerial supervision carried out by school staffers is carried out according to the prescribed procedures. Various efforts are made by the school superintendent in conducting construction and supervision to the built school. In the process of managerial supervision, school superintendents sometimes experience obstacles because they are done online. This constraint makes school supervisors creative in the managerial supervision process by optimizing existing digital platforms to improve quality (quality) through quality assurance of education in schools.